Adsortion of metal ions (Camium, copper, lead, silver and zinc) on nata de coco - Morales,Jim Carlo
The metal toxicity of cadmium, copper, lead, silver and zinc on cellulose production of Glucoacetobacter xylimus was investigated. After 3 days of incubation period, grown metalized cellulose were harvested, dried and analyzed for ion interaction by FTIR and metal adsorption by F-AAS. The metals in the cellulose matrix were reduced to its sulfide form but treating it with 5% thioacetamide solution and conuctance was later measured by using a multitester device.